Eksplorasi Pertumbuhan Spiritual Dan Perkembangan Manusia Pada Anak-anak Dan Remaja: Perspektif Teologi - Megawaty, Titin; Herman, Samuel (Sekolah Tinggi Teologi Aletheia, 2024)
Abstract:This article integrates theological perspectives with insights from human development experts to understand the processes of growth and development in individuals. Specifically, it focuses on the phases from childhood to adolescence, which are crucial in shaping one's personality and beliefs. The research explores the roles of parents, church communities, and educators in guiding children towards healthy spiritual growth. Additionally, it analyses how Jesus, as an example of spiritual growth and development, inspires the current generation. The implications outlined in this study highlight the importance of understanding morals, religious education, and spiritual identity formation during adolescence, as efforts to help individuals find meaning in life. Abstrak:Artikel ini menyatukan perspektif teologi dan pandangan ahli perkembangan manusia dalam memahami proses pertumbuhan dan perkembangan individu. Terutama, artikel ini menitikberatkan pada fase anak-anak hingga remaja, yang memegang peranan penting dalam pembentukan kepribadian dan keyakinan seseorang. Penelitian ini mengeksplorasi peran orang tua, komunitas gereja, dan pendidik dalam membimbing anak-anak menuju pertumbuhan rohani yang sehat. Selain itu, penelitian juga menganalisis bagaimana Yesus sebagai contoh dalam pertumbuhan dan perkembangan rohani memberikan inspirasi bagi generasi saat ini. Implikasi yang diuraikan dalam penelitian ini menunjukkan pentingnya pemahaman mengenai moral, pendidikan agama, dan pembentukan identitas rohani pada masa remaja, sebagai upaya untuk membantu individu menemukan makna dalam hidup.